Benzodiazepine use in Sao Paulo, Brazil (Clinics, 2020)
OBJECTIVES: To report the prevalence and factors associated with the use of benzodiazepines in the general population and those with a mental health condition in the metropolitan area of Sa˜o Paulo, Brazil. METHODS: 5,037 individuals from the Sao Paulo Megacity Mental Health Survey data were interviewed using the Composite International Diagnostic Interview, designed to generate DSM-IV diagnoses. Additionally, participants were asked if they had taken any medication in the previous 12 months for the treatment of any mental health condition. RESULTS: The prevalence of benzodiazepine use ranged from 3.6% in the general population to 7.8% among subjects with a mental health condition. Benzodiazepine use was more prevalent in subjects that had been diagnosed with a mood disorder as opposed to an anxiety disorder (14.7% vs. 8.1%, respectively). Subjects that had been diagnosed with a panic disorder (33.7%) or bipolar I/II (23.3%) reported the highest use. Individuals aged X50 years (11.1%), those with two or more disorders (11.2%), those with moderate or severe disorders (10%), and those that used psychiatric services (29.8%) also reported higher use. CONCLUSION: These findings give an overview of the use of benzodiazepines in the general population, which will be useful in the public health domain. Benzodiazepine use was higher in those with a mental health condition, with people that had a mood disorder being the most vulnerable. Furthermore, females and the elderly had high benzodiazepine use, so careful management in these groups is required.